2021
DOI: 10.1111/bcp.15149
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and novel therapeutic options in children with familial Mediterranean fever: A rare autoinflammatory disease

Abstract: Familial Mediterranean fever (FMF) is the most common monogenic autoinflammatory disease and is usually diagnosed in childhood, especially in the first decade of life. Paediatric FMF is characterized by a protean clinical expression and a variable therapeutic response, which can make its medical management very challenging. However, even if long-term complications of untreated FMF (e.g. amyloidosis and related organ damage) are less frequent in children compared to adults, they are not uncommon. Colchicine is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
(247 reference statements)
0
7
0
Order By: Relevance
“…Since 1972, colchicine has been used to prevent attacks and renal amyloidosis in FMF. Colchicine is an alkaloid extracted from the colchicum autumnale plant [2]. It inhibits neutrophil chemotaxis and activity in response to vascular injury and in ammasome signaling, decreases active interleukin-1β production, reduces neutrophil-platelet interaction and aggregation, and ultimately suppresses in ammation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1972, colchicine has been used to prevent attacks and renal amyloidosis in FMF. Colchicine is an alkaloid extracted from the colchicum autumnale plant [2]. It inhibits neutrophil chemotaxis and activity in response to vascular injury and in ammasome signaling, decreases active interleukin-1β production, reduces neutrophil-platelet interaction and aggregation, and ultimately suppresses in ammation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Poddighe et al discuss how the promising use of anti-TNF molecules for FMF Gene therapy required the utilization of a safe delivery vehicle/ vector to ensure an efficient transfer for such therapy to be successful. 5,17 Precision medicine and genetics have guided the development of novel treatments in rare epilepsies. In their review on this topic for this special issue, Marini and Giardino 18 explain how next generation techniques have led to a more precise genetic aetiology in up to 50% of paediatric genetic epilepsies and has given a better understanding of the mechanisms underlying these conditions.…”
mentioning
confidence: 99%
“…The repurposing of old drugs is often the first avenue of choice in this search. In their review for this issue, Poddighe et al 5 showed how the repurposing of old drugs, such as colchicine, resulted in an effective treatment for familial Mediterranean fever, an autoinflammatory disease. However, alternatives are needed for those patients who are resistant to this type of therapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations